Accelerated re-epithelialization of partial-thickness skin wounds by a topical betulin gel: Results of a randomized phase III clinical trials program - Barret-Nerín, Juan Pedro; Podmelle, Fred; Lipový, Břetislav; Rennekampff, Hans-Oliver; Schumann, Hauke; Schwieger-Briel, Agnes; Zahn, Tobias R; Metelmann, Hans-Robert (Burns, 2017)
The clinical significance of timely re-epithelialization is obvious in burn care, since delayed wound closure is enhancing the risk of wound site infection and extensive scarring. Topical treatments that accelerate wound healing are urgently needed to reduce these sequelae. Evidence from preliminary studies suggests that betulin can accelerate the healing of different types of wounds, including second degree burns and split-thickness skin graft wounds. The goal of this combined study program consisting of two randomized phase III clinical trials in parallel is to evaluate whether a topical betulin gel (TBG) is accelerating re-epithelialization of split-thickness skin graft (STSG) donor site wounds compared to standard of care. Two parallel blindly evaluated, randomised, controlled, multicentre phase III clinical trials were performed in adults undergoing STSG surgery (EudraCT nos. 2012-003390-26 and 2012-000777-23). Donor site wounds were split into two equal halves and randomized 1:1 to standard of care (a non-adhesive moist wound dressing) or standard of care plus TBG consisting of 10% birch bark extract and 90% sunflower oil (Episalvan, Birken AG, Niefern-Oeschelbronn, Germany). The primary efficacy assessment was the intra-individual difference in time to wound closure assessed from digital photographs by three blinded experts. A total of 219 patients were included and treated in the two trials. Wounds closed faster with TBG than without it (15.3 vs. 16.5 days; mean intra-individual difference=-1.1 days [95% CI, -1.5 to -0.7]; p<0.0001). This agreed with unblinded direct clinical assessment (difference=-2.1 days [95% CI, -2.7 to -1.5]; p<0.0001). Adverse events possibly related to treatment were mild or moderate and mostly at the application site. TBG accelerates re-epithelialization of partial thickness wounds compared to the current standard of care, providing a well-tolerated contribution to burn care in practice.
Keywords: Surgical Wound; dospělí; Skin Transplantation; Female; Gels; transplantace kůže; Adult; výsledek terapie; ženské pohlaví; aplikace kožní; lidé; Administration, Cutaneous; Treatment Outcome; triterpeny; Male; Aged; gely; Burns; Re-Epithelialization; Triterpenes; lidé středního věku; chirurgická rána; senioři; mužské pohlaví; popálení; Middle Aged; reepitalizace; Humans